In vivo evaluation of a polyester and fiberglass composite intramedullary nail for femoral osteosynthesis in calves - Sérgio Silva Rocha Junior; Mayara G. Corrêa; Lucas A. Dias; Marcos Paulo Antunes de Lima; Suzane L. Beier; Leopoldo Paolucci; Luiz Alberto do Lago; Estevam B. Las Casas; Rafael R. Faleiros (PeerJ, 2024)
The objective of this study was to test a composite of polyester resin and fiberglass in the form of an intramedullary nail for osteosynthesis of femoral fractures in calves. The methodology was established based on a previous study that used a bovine femur finite element model to simulate fractures, which were then stabilized by the same nails as proposed in this study. General anesthesia was induced in six calves followed by fracture creation via an oblique incision in the middle third of the femoral diaphysis, and osteosynthesis was immediately performed by retrograde insertion of the composite nail. Locking was achieved by drilling the bone and nail without using a jig and introducing two stainless steel screws proximal and two distal to the fracture line. Five of the six calves achieved complete fracture healing after 60 days. No signs of incompatibility or toxicity of the composite were observed. However, limitations were observed during the surgery, such as difficulty in drilling the nail and trimming the remainder portion of the nail that extended beyond the length of the bone. Small fragments produced by these maneuvers were considered irritating to soft tissues during the postoperative period. It was also found that small cracks in the nail tended to propagate in the form of longitudinal fractures. In conclusion, an intramedullary nail made of polyester resin and fiberglass (a low-cost and easy-to-acquire material) was considered biocompatible and capable of allowing bone healing of femoral fractures in young cattle. However, the development of solutions for the reported limitations is crucial prior to recommending the proposed composite for clinical use.